2016
DOI: 10.1097/spv.0000000000000233
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Prolapse Stage as Predictor of Failure of Sacrocolpopexy

Abstract: Much like a higher stage of disease in oncology, we found that increasing stage of prolapse preoperatively increased the risk of recurrence at 1 year after sacrocolpopexy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…Postoperatively a higher percentage of recurrent cystocele was seen after RSHS, which could possibly be explained by the higher sPOPQ stage A reported preoperatively, this is associated with a higher risk of recurrence . Comparisons between the two types of surgeries must be analysed carefully, however, as this study was not set up as a randomised controlled trial.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperatively a higher percentage of recurrent cystocele was seen after RSHS, which could possibly be explained by the higher sPOPQ stage A reported preoperatively, this is associated with a higher risk of recurrence . Comparisons between the two types of surgeries must be analysed carefully, however, as this study was not set up as a randomised controlled trial.…”
Section: Discussionmentioning
confidence: 99%
“…The use of anterior vaginal mesh in particular has been associated with a higher apical recurrence rate as opposed to the SSLF procedure where there appears to be more of a risk for a recurrent cystocele [24]. It is also appreciated that the present clinical methods do not sufficiently predict the outcome of specific operative approaches [25,26] particularly where there is no consensus regarding what represents a surgical success. Future prospective work will be required to define whether symptoms relate more readily to the measurable ordinal POP-Q values rather than to a particular POP stage with the most distal point more closely reflecting an anatomical (as opposed to a stage) correction [27].…”
Section: Discussionmentioning
confidence: 99%
“…In that study, the success rates dropped to 50-60% for the same procedures when they were performed for recurrent prolapse (44). A multicenter cohort study demonstrated that a higher preoperative prolapse stage increased the risk of recurrence at 1 year by a factor of 3.8 (45). Like in cancer surgery, standard therapies are less effective when used on the more advanced and recurrent disease.…”
Section: Ancillary Factors Impacting Efficacymentioning
confidence: 99%